2009
DOI: 10.1002/cphc.200900240
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophores as Optical Sensors for Local Forces

Abstract: The main aim of this study is to investigate correlations between the impact of an external mechanical force on the molecular framework of fluorophores and the resultant changes in their fluorescence properties. Taking into account previous theoretical studies, we designed a suitable custom-tailored oligoparaphenylenevinylene derivative (OPV5) with a twisted molecular backbone. Thin foils made of PVC doped with 100 nM OPV were prepared. By applying uniaxial force, the foils were stretched and three major optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Recent advances in the incorporation of force‐responsive units, so‐called mechanophores, into the backbones of polymers have allowed the synthesis of a prototypical molecular force sensor, in which the mechanically induced isomerization of spiropyran to merocyanin is accompanied by a color change of the material from yellow to red . While several molecular force sensors based on changes in their vibrational, UV/Vis, fluorescence,, or chemiluminescence spectra have been reported, an ongoing challenge in the design of novel molecular force sensors is the need to generate a measurable spectral change well before material failure occurs. Using computational methods, it is here demonstrated that the mechanically induced switching of aromaticity and homoaromaticity in molecular force sensors are convenient approaches to achieve substantial changes in color at low stretching forces.…”
Section: Methodsmentioning
confidence: 99%
“…Recent advances in the incorporation of force‐responsive units, so‐called mechanophores, into the backbones of polymers have allowed the synthesis of a prototypical molecular force sensor, in which the mechanically induced isomerization of spiropyran to merocyanin is accompanied by a color change of the material from yellow to red . While several molecular force sensors based on changes in their vibrational, UV/Vis, fluorescence,, or chemiluminescence spectra have been reported, an ongoing challenge in the design of novel molecular force sensors is the need to generate a measurable spectral change well before material failure occurs. Using computational methods, it is here demonstrated that the mechanically induced switching of aromaticity and homoaromaticity in molecular force sensors are convenient approaches to achieve substantial changes in color at low stretching forces.…”
Section: Methodsmentioning
confidence: 99%
“…These variations may involve mass transfer, heating, mechanical stress generation/relaxation, or redistribution of electronic or ionic charges . In particular, the capability to control the optical properties of molecules by a mechanical stress can activate or deactivate chemical reactions, and enable new functionalities for monitoring and sensing . This is both a fundamental challenge in the broad field of nanosciences and a significant advantage for applications in medical diagnostics and for signal transduction in biointerfaces.…”
mentioning
confidence: 99%
“…Recently, anisotropic compressive stresses at nN‐scale have been found to induce photophysical changes in conjugate polymer nanoparticles and in single organic dye molecules . In another report, uniaxial tensile forces have been applied to polymer foils doped with an oligo‐paraphenylenevinylene derivative, leading to a blueshift of the emission by 1.2 nm . With focus on practical applications, the capability to control electro‐optical processes through the modification of a piezoelectric potential, in turn led by an external stress, has been introduced by the Wang's group in 2010 .…”
mentioning
confidence: 99%
See 2 more Smart Citations